PENERAPAN KONSEP MULTIPLE INTELLIGENCES PADA PEMBELAJARAN PAI - Fikriyah, Fuji Zakiyatul; Aziz, Jamil Abdul (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2018)
This paper aims to explain how the application of the concept of Multiple Intelligences was coined by Howard Gardner at the School of Human (SOH) on Islamic Religious Education (PAI) in Bekasi, West Java. This type of research is field research and is presented in descriptive form. While the approach taken is a qualitative approach. Data collection techniques used: observation, interviews, and documentation. The results showed that the implementation of the concept of multiple intelligences in the learning of Islamic religious education (PAI) in Cibubur School of Human (SOH) Junior High School in grades VIII and IX, namely the implementation of multiple intelligences in learning requires teachers to have creativity in applying the concept of multiple intelligences. At SMP Cibubur's School of Human (SOH) learning Islamic religious education (PAI) with multiple intelligences approaches varies greatly. The teacher uses varied perceptions, diverse strategies and methods, and is supported by the use of creative media.